The Status of Human Echinococcosis in Western Mongolia - Dorjsuren, Temuulen; Narantsogt, Giimaa; Davgasumberel, Munkhbaatar; Ganbat, Mandukhai; Sumiya, Ganzorig; Damdinsuren, Boldbaatar; Tsevelvaanchig, Uranchimeg; Boldbaatar, Chinchuluun; Jamiyansuren, Jambaldorj; Orgoi, Sergelen; Ayushkhuu, Tsendjav; Bayarlakh, Javkhlantur; et al. (Central Asian Journal of Medical Sciences, 2019)
Objective: The purpose of this study was to identify cases of human echinococcosis in the Bayan-Ulgii, Khovd provinces, to determine their WHO classification by ultrasound and to identify the haplotype in surgically cysts removed. Methods: A total of 1063 people participated in ultrasound screening. Patients who had a positive echinococcosis by ultrasound underwent serologic testing for detection of antibodies for echinococcosis. Results: Ninety people were positive for the liver cystic lesions by ultrasound screening of which 12 cases were newly diagnosed cystic echinococcosis. Four were cystic echinococcosis stages 1-2, five were stage 3, while three were cystic echinococcosis stage 4. Thirty-three patients with previously known echinococcosis stage 2 and alveolar echinococcosis stage 4 were also examined. Out of 29 cystic echinococcosis cases, 24 underwent treatment. Of 24 who underwent treatment, only one was cured. The haplotypes E. canadensis G6/7 and E. granulossus s.s. G1 were confirmed by evaluating the cytochrome c oxidase subunit I gene of mitochondrial DNA in two patients in Bayan-Ulgii. Conclusion: Ninety people were positive for cystic echinococcosis in western Mongolia of which 12 cases were newly diagnosed cases. Of the 12 new cystic echinococcosis cases, 4 were stages 1-2, 5 were stage 3 and 3 were stage 4 by WHO classification. The haplotype in Bayan-Ulgii population were E. canadensis and s.s.